Leucine-rich glioma-inactivated 1 versus contactin-associated protein-like 2 antibody neuropathic pain: clinical and biological comparisons - Ramanathan, S; Tseng, M; Davies, AJ; Uy, CE; Paneva, S; Mgbachi, VC; Michael, S; Varley, JA; Binks, S; Themistocleous, AC; Fehmi, J; Anziska, Y; et al. (Wiley, 2021)
Pain is a under-recognized association of leucine-rich glioma-inactivated 1 (LGI1) and contactin-associated protein-like 2 (CASPR2) antibodies. Of 147 patients with these autoantibodies, pain was experienced by 17 of 33 (52%) with CASPR2- versus 20 of 108 (19%) with LGI1 antibodies (p = 0.0005), and identified as neuropathic in 89% versus 58% of these, respectively. Typically, in both cohorts, normal nerve conduction studies and reduced intraepidermal nerve fiber densities were observed in the sampled patient subsets. In LGI1 antibody patients, pain responded to immunotherapy (p = 0.008), often rapidly, with greater residual patient-rated impairment observed in CASPR2 antibody patients (p = 0.019). Serum CASPR2 antibodies, but not LGI1 antibodies, bound in vitro to unmyelinated human sensory neurons and rodent dorsal root ganglia, suggesting pathophysiological differences that may underlie our clinical observations.